Modeling the interaction of cytotoxic T lymphocytes and influenzavirus infected epithelial cells - Abdessamad Tridane; Yang Kuang (Mathematical Biosciences and Engineering)
The aim of this work is to investigate the mechanisms involved in the clearance ofviral infection of the influenza virus at the epithelium level by modeling and analyzingthe interaction of the influenza virus specific cytotoxic T Lymphocytes (CTL cells) and theinfluenza virus infected epithelial cells. Since detailed and definite mechanisms thattrigger CTL production and cell death are still debatable, we utilize two plausiblemathematical models for the CTLs response to influenza infection (i) logisticgrowth and (ii) threshold growth. These models incorporate the simulatingeffect of the production of CTLs during the infection. The systematicalanalysis of these models show that the behaviors of the models are similar when CTLdensity is high and in which case both generate reasonable dynamics. However, bothmodels failed to produce the desirable and natural clearance dynamic.Nevertheless, at lower CTL density, the threshold model shows the possibility ofexistence of a 'lower' equilibrium. This sub-threshold equilibrium may representdose-dependent immune response to low level infection.